Forgetting fire: Traditional fire knowledge in two chestnut forest ecosystems of the Iberian Peninsula and its implications for European fire management policy. (September 2015) - Seijo, Francisco; Millington, James D.A.; Gray, Robert; Sanz, Verónica; Lozano, Jorge; García-Serrano, Francisco; Sangüesa-Barreda, Gabriel; Julio Camarero, Jesús
Highlights: We compare the impact of state fire exclusion policies in two chestnut forest ecosystems. Our analysis integrates biophysical and human system methodologies and evidence. Differences between forests are useful for considering traditional fire knowledge. Our findings are contrasted with those of the E.U. sponsored Fire Paradox project. Abstract: Human beings have used fire as an ecosystem management tool for thousands of years. In the context of the scientific and policy debate surrounding potential climate change adaptation and mitigation strategies, the importance of the impact of relatively recent state fire-exclusion policies on fire regimes has been debated. To provide empirical evidence to this ongoing debate we examine the impacts of state fire-exclusion policies in the chestnut forest ecosystems of two geographically neighbouring municipalities in central Spain, Casillas and Rozas de Puerto Real. Extending the concept of 'Traditional Ecological Knowledge' to include the use of fire as a management tool as 'Traditional Fire Knowledge' (TFK), we take a mixed-methods and interdisciplinary approach to argue that currently observed differences between the municipalities are useful for considering the characteristics of "pre-industrial anthropogenic fire regimes" and their impact on chestnut forest ecosystems. We do this by examining how responses from interviews and questionnaire surveys of local inhabitants about TFK in the past and present correspond to the current biophysical landscape state and recent fire activity (based on data from dendrochronological analysis, aerial photography and official fire statistics). We then discuss the broader implications of TFK decline for future fire management policies across Europe particularly in light of the published results of the EU sponsored Fire Paradox research project. In locations where TFK-based "pre-industrial anthropogenic fire regimes" still exist, ecosystem management strategies for adaptation and mitigation to climate change could be conceivably implemented at a minimal economic and political cost to the state by local communities that have both the TFK and the adequate social, economic and cultural incentives to use it.